The Exceptional Teacher Initiative: Finding a Silver Lining in Addressing Medical Student Mistreatment. (July 2019) - Blackall, George F.; Wolpaw, Terry; Shapiro, Dan
Abstract : Problem: The Penn State College of Medicine (PSCOM) faced escalating reports of learner mistreatment in 2013–2017. As systems were implemented to gather and respond to student reports, faculty members expressed concern that these were creating a culture that focused on negative behaviors to the exclusion of acknowledging outstanding teaching that was also occurring. Approach: The Exceptional Teacher Initiative was introduced in August 2017 to attempt to shift the institutional conversation around learner mistreatment by balancing reports of mistreatment with reports highlighting examples of excellent teaching considered in-line with organizational values. The primary goals of the program were to make it easy for students to submit narratives describing outstanding teaching experiences and to capture the nuances of what the teacher did that were notable to the student. Students were invited to write about teachers who challenged and changed them. Narratives were sent to the named teachers and their educational and clinical leaders. Outcomes: Over the first 12 months of the Exceptional Teacher Initiative, learners submitted 553 narratives naming 253 different individuals across 37 departments. Faculty members and students expressed appreciation for this effort to highlight the positive. A monthly Exceptional Moments in Teaching feature was introduced in 2018, in which a named educator is featured prominently across the PSCOM. Next Steps: Future plans include examining the impact of being named an exceptional teacher, ways exceptional teachers create respectful teaching interactions, and common threads within student narratives that illuminate specific techniques, behaviors, and attitudes that create exceptional teaching experiences. Abstract : Supplemental Digital Content is available in the text.